1975
DOI: 10.1029/jb080i029p04049
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical single-domain grain size range in magnetite and titanomagnetite

Abstract: A theoretical model of single‐domain (SD) grain sizes is applied to magnetite and titanomagnetite. In this model, transition to a two‐domain configuration takes place at the SD threshold d0. This two‐domain configuration is shown to be more applicable to fine‐grained magnetites in igneous rocks than previous models involving transition to a circular spin configuration at d0. Calculations of the stable SD grain size range were accomplished by calculating the superparamagnetic threshold size ds by Néel's relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
326
1
3

Year Published

1990
1990
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 524 publications
(356 citation statements)
references
References 32 publications
26
326
1
3
Order By: Relevance
“…The species-specific crystals produced by MV-1 are matched to their func tional requirement as organelles responsible for magnetotactic behaviour. In this respect, the par ticle size range of MV-1 crystals falls within that required for single domain remanent magnetiza tion (35-100 nm) [14], whereas the smaller GS-15 crystals are superparamagnetic. The latter be haviour results in the spectral broadening, caused by relaxation effects, observed in the M6ssbauer spectra (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The species-specific crystals produced by MV-1 are matched to their func tional requirement as organelles responsible for magnetotactic behaviour. In this respect, the par ticle size range of MV-1 crystals falls within that required for single domain remanent magnetiza tion (35-100 nm) [14], whereas the smaller GS-15 crystals are superparamagnetic. The latter be haviour results in the spectral broadening, caused by relaxation effects, observed in the M6ssbauer spectra (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Length and shape factor (width/length ratio) of magnetite particles from 168.81 m depth. The lower, SD/ superparamagnetic boundary is determined for rectangular parallelepipeds with unblocking times of 100 s (bottom dashed line) and 4.5 Ga (bottom solid line) [Butler and Banerjee, 1975;Diaz-Ricci and Kirschvink, 1992]. The top solid line and top dashed line show the upper boundary of the metastable single-domain field and stable single-domain field, respectively [Witt et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of particle size and shape on the magnetic state of an isolated magnetite particle was discussed theoretically by Butler & Banerjee (1975), who suggested that the transition from single-domain to superparamagnetic behavior occurs below a particle size of 25-30 nm. Figure 9 shows local magnetic structures of magnetite particle assemblies on smectite (clay) platelets, which provide an ideal geometry for the experimental study of the critical threshold size for superparamagnetic behavior in the presence of strong interactions between adjacent particles (Galindo-Gonzalez et al, 2009).…”
Section: Critical Size For Superparamagnetic Behavior In Three-dimensmentioning
confidence: 99%